Mosaic Analysis with Double Markers Reveals Tumor Cell of Origin in Glioma - Liu, Chong; Sage, Jonathan C.; Miller, Michael R.; Verhaak, Roel G.W.; Hippenmeyer, Simon; Vogel, Hannes; Foreman, Oded; Bronson, Roderick T.; Nishiyama, Akiko; Luo, Liqun; Zong, Hui (Cell, 2011)
Cancer cell of origin is difficult to identify by analyzing cells within terminal stage tumors, whose identity could be concealed by the acquired plasticity. Thus, an ideal approach to identify the cell of origin is to analyze proliferative abnormalities in distinct lineages prior to malignancy. Here, we use mosaic analysis with double markers (MADM) in mice to model gliomagenesis by initiating concurrent p53/Nf1 mutations sporadically in neural stem cells (NSCs). Surprisingly, MADM-based lineage tracing revealed significant aberrant growth prior to malignancy only in oligodendrocyte precursor cells (OPCs), but not in any other NSC-derived lineages or NSCs themselves. Upon tumor formation, phenotypic and transcriptome analyses of tumor cells revealed salient OPC features. Finally, introducing the same p53/Nf1 mutations directly into OPCs consistently led to gliomagenesis. Our findings suggest OPCs as the cell of origin in this model, even when initial mutations occur in NSCs, and highlight the importance of analyzing premalignant stages to identify the cancer cell of origin. [Display omitted] ► Modeling human glioma using mosaic analysis with double markers (MADM) ► Tracking lineage-specific aberrant growth at pretransformation stages ► Oligodendrocyte precursor cells (OPCs) are a cell of origin for glioma ► Cancer cell of mutation and cell of origin are distinct